Analisis Populasi dan Tingkat Serangan Liriomyza huidobrensis pada Empat Varietas Kentang Industri di Wilayah Sembalun, Lombok Timur - Malasari; Sarjan, Muhammad; Kisman (Journal of Microbiology, Biotechnology and Conservation, 2025)
This study aimed to analyze the population dynamics and attack intensity of the leafminer fly Liriomyza huidobrensis on four industrial potato varieties cultivated in Sembalun, East Lombok. A field experimental method was employed using a Randomized Block Design (RBD) consisting of four treatments, namely Mc. Russet (A), Ranger Russet (B), Chitra (C), and Atlantic (D), each replicated six times to obtain 24 experimental units. The results revealed that Mc. Russet and Ranger Russet exhibited greater resistance to L. huidobrensis compared to Chitra and Atlantic. The population of the leafminer fluctuated throughout the observation period, with the highest population recorded at 63–70 days after planting (DAP) on the Atlantic variety (2.22 individuals per plant), while the lowest was observed on Mc. Russet (1.14 individuals per plant). Similarly, the intensity of attack varied among varieties, with the highest recorded on Atlantic at 63–70 DAP (4.65%) and the lowest on Mc. Russet (3.1%). These findings confirm the existence of varietal differences in resistance to L. huidobrensis and provide important implications for varietal selection in integrated pest management strategies in the Sembalun region.